Pendampingan Program Pengayaan Ekstrakurikuler di SD/MI Bahagia, Wonokromo, Surabaya - Savira, Siti Ina; Syafiq, Muhammad; Dewi, Damajanti Kusuma; Nurwidawati, Desi (Universitas Pendidikan Ganesha, 2018)
Abstract This paper is aimed to describe extracuricular advocacy activity at Islamic Primary School Bahagia, Wonokromo, Surabaya, as a community service conducted by team of lecturers of Universitas Negeri Surabaya. This school is particularly chosen because it has a unique social-economy background and limitations. The advocacy provided was to improve teachers’ soft-skills and creativity to be able to design supplementary activities to help students grow their interest and soft-skill as well. The final outcome is to see students’ growth in self-confidence, team work, respct and toleration to each other, which also support their academic achievement.